Smart Cane for Assisting Visually Impaired People and the Blind - Kramomthong, P.; Pintavirooj, C.; Paing, May Phu (My University, 2021)
The limited mobility of the visually impaired and blind makes daily activities such as avoiding obstacles, traveling, crossing the street, and dealing with an emergency difficult. Currently, there are active studies and developments about devices and technologies that increase deftness daily and travel independently. In this paper, we combine various functions into one device consisting of obstacle detection, navigation, and emergency calls to increase the safety and travel mobility of visually impaired people and the blind. The laboratory experiment results of whole functions were successful, and the device can alert the user with sound and vibration.
Keywords: Emergency call; Navigation; Obstacle detection; Safety and travel mobility